Developmental improvements in the ability to benefit from testing across middle childhood - Rodríguez-Gonzalo, Sandra; Arnaez-Telleria, Jaione; Paz-Alonso, Pedro M. (Frontiers in Behavioral Neuroscience, 2024)
Extensive behavioral research on adults has shown that retrieval practice is highly beneficial for long-term memory retention. However, limited evidence exists on the developmental course of this benefit. Here, we present data from a behavioral study involving 7–14-year-old children who had to encode a total of 60 weakly semantically related cue-target word pairs using either repeated retrieval or repeated study encoding strategies. Results revealed age-related increases in the ability to benefit from testing during encoding from early middle childhood to early adolescence. In contrast, repeated study during encoding did not lead to developmental improvements in long-term memory retention across this age range. Individual differences in vocabulary knowledge, short-term memory and working memory were positively associated with long-term memory retention only for those participants who encoded the information via repeated study. These results indicate that (1) the mechanisms determining the testing effect may not be fully in place by early middle childhood, (2) the ability to benefit from testing improves over the middle childhood years, and (3) these benefits are not associated with individual differences in memory and high-cognitive functioning. One potential interpretation of these findings is that changes in sleep-dependent consolidation processes during middle childhood may be critical for understanding the observed developmental differences in ability to enhance long-term memory via the testing effect.